Differences in Carotid Intima-Media Thickness (CIMT) In Patients With Newly Diagnosed Hypertension, and Chronic Hypertensive Patients Treated by Calcium Channel Blockers (CCB) or Angiotensin Converting Enzyme (ACE)-Inhibitors - Tantri, Ni Luh; Rudijanto, Achmad; Samsu, Nur; Wursito, Wursito (Universitas Brawijaya, 2020)
Â Hypertension is a significant risk factor for cardiovascular diseases. It closely related to the inflammatory process and resulting in chronic inflammation, which had a critical role in the progression of atherosclerosis. Carotid Intima-Media Thickness (CIMT) was known as a surrogate marker of atherosclerosis. Anti-hypertensive drugs are expected to affect CIMT. Aim: to examine the difference CIMT between newly diagnosed hypertension and chronic hypertensive treated by ACE-I or CCB. Method: this cross-sectional study was conducted on 12 newly diagnosed hypertensive patients (control or group 1), 9 hypertensive patients treated by CCB (group 2), and 9 hypertensive patients treated by ACE-I (group 3). Their hypertensive condition was controlled at least for 6 months. We compared CIMT of patients and Tumour Necrosis Factor Alfa (TNF-Î±) also Interleukin-6 (IL-6) among the groups. Result: there was a significant difference in CIMT between the group 1 and 2 (0.86 vs 0.70; p = 0.027), group 1 and 3 (0.86 vs 0.69; p = 0.018). There was no significant difference between group 2 and 3 (0.70 vs 0.69; p = 0.88). There was no association between CIMT and TNF-Î±, IL-6, Low-Density Lipoprotein (LDL), triglycerides (TGs) levels, and body mass index (BMI), systolic blood pressure. Conclusion: we found that the CIMT of the control group was thicker than those of the treatment groups. Moreover, differences in the thickness of CIMT of the three groups were not associsted with level of TNF-Î±, IL-6, TG, and LDL, also BMI, and systolic blood pressure.